Deep Brain Stimulation in Epilepsy: A Role for Modulation of the Mammillothalamic Tract in Seizure Control?. (18th November 2021) - Schaper, Frédéric L W V J; Plantinga, Birgit R; Colon, Albert J; Wagner, G Louis; Boon, Paul; Blom, Nadia; Gommer, Erik D; Hoogland, Govert; Ackermans, Linda; Rouhl, Rob P W; Temel, Yasin
Graphical Abstract: